Simultaneous encapsulation of echium (Echium Plantagineum L.) seed oil, phytosterols and phenolic compounds: characterization and application of microcapsules - Comunian, Talita Aline (2017)
The consumption of omega-3 fatty acids and phytosterol promotes the reduction of cholesterol and triacylglycerol levels. However, such compounds are susceptible to oxidation, which hampers their application. First, the aim of this work was to encapsulate echium oil (Echium plantagineum L.), source of omega-3 fatty acids, with hydrophilic phenolic compounds (sinapic acid and rutin) by double emulsion followed by complex coacervation in order to evaluate the best hydrophilic phenolic compound. In this case, sinapic acid showed better performance as antioxidant. Then, the second objective of this work was to study the microencapsulation of echium oil by complex coacervation using gelatin-arabic gum and gelatin-cashew gum as wall materials and sinapic acid and transglutaminase as crosslinkers. In this step, it was possible to observe that sinapic acid, besides to be an antioxidant, could also act as crosslinker. So, the third objective was to study the effect of sinapic acid in echium microparticles obtained by emulsion followed by spray or freeze drying using arabic gum as carrier agent in order to compare different encapsulation techniques. In addition to these methods, the fourth objective was to compare these techniques already mentioned to the combination of microfluidic devices and ionic gelation in order to encapsulate echium oil. In this case, sinapic acid and quercetin were also incoporated in the microcapsules. All the microcapsules/ microparticles obtained in the mentioned different techniques presented characteristics feasible for application and also promoted the protection of the oil. However, the encapsulation by complex coacervation and the addition of sinapic acid as crosslinkers was the method choosen for the coencapsulation of echium oil and phytosterols since presented the better results. Moreover, the treatment GA075 (microcapsule with gelatin-arabic gum as wall materials and 0.075g sinapic acid/ g gelatin) promoted the better protection to the encapsulated compounds. In this way, this treatment was applied into yogurt and compared to the one with the compounds nonencapsulated and the yogurt control. The yogurt containing microcapsules, presented a pH range from 3.89-4.17 and titratable acidity range from 0.798-0.826%, with good sensorial acceptance. It was possible to apply the microcapsules in yogurt, without compromising the rheological properties and physicochemical stability of the product, obtaining a functional product rich in omega-3 fatty acids, phytosterols and phenolic compound.